Short tandem repeat genotypes of samples from eleven populations comprising the FBI’s population database - Lilliana I. Moreno; Tamyra R. Moretti (Forensic Science International: Reports, 2019)
Electronic DNA genotype data corresponding to eleven FBI relevant populations, typed with the expanded STR chemistries, are presented. Such data may prove valuable for population genetic studies and other forensic relevant inquiries. Keywords: FBI populations, Genotypes, Expanded core loci